2019
DOI: 10.15537/smj.2019.11.24587
|View full text |Cite|
|
Sign up to set email alerts
|

Influenza vaccine coverage, awareness, and beliefs regarding seasonal influenza vaccination among people aged 65 years and older in Central Saudi Arabia

Abstract: Objectives: To investigate the level of awareness, sources of knowledge, and beliefs about the influenza vaccine in people ≥65 years in central Saudi Arabia. Methods: A cross-sectional study that used self-administered questionnaires conducted in 3 primary healthcare centers in Riyadh, Saudi Arabia between May 2018 and August 2018. Results: There were 496 Saudis participants (70.2% male) were included, of whom, 47.8% had been vaccinated against influenza at least once. Of unvaccinated individuals, 46% believed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 16 publications
2
21
2
2
Order By: Relevance
“…From 2006, published studies from Saudi Arabia tried to calculate the SIV coverage rates among some risk groups but not among the general population ( Appendix 2 ). Among those studies, most of them reported that the targeted risk group was HCWs with variable coverage percentages from 5.9% up to 54.5% [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ]. In this study, the SIV coverage rate of HCWs was 42.9%, which seems higher than the median yearly HCW coverage rate (33.3%) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2006, published studies from Saudi Arabia tried to calculate the SIV coverage rates among some risk groups but not among the general population ( Appendix 2 ). Among those studies, most of them reported that the targeted risk group was HCWs with variable coverage percentages from 5.9% up to 54.5% [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ]. In this study, the SIV coverage rate of HCWs was 42.9%, which seems higher than the median yearly HCW coverage rate (33.3%) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This low rate of vaccinated patients with diabetes may be related to change in health priorities and behaviors during the COVID-19 pandemic. In the other two studies, the coverage rates of SIV among older people and pregnant women were 47.8% and 18.1%, respectively [ 33 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acceptance rate for the COVID-19 vaccine in our study (39.8%) was less compared to that in other countries such as China (90%), Brazil (86%), the United States (75.4%), India (74.3%), and Russia (55%) [18] . Previous studies done in the Kingdom regarding vaccine acceptance for different diseases have reported a comparatively good acceptance rate for seasonal influenza [19,20] , whereas a poor acceptance rate has been reported for the H1N1 vaccine [21] . The lowered acceptance rate in our study could be due to rumors spreading on social media and some misconceptions about the vaccine which include but are not limited to the belief that there is an electronic chip in the vaccine, that it affects fertility and other mistaken beliefs about side effects.…”
Section: Discussionmentioning
confidence: 91%
“…Na China, ser do sexo feminino, ter doença crônica, participar de atividades comunitárias e receber recomendações de provedores de cuidados de saúde foram associados à maior vacinação, evidenciando a importância da disseminação de conhecimentos sobre a necessidade da vacina 14 . Na Arábia Saudita, as pessoas idosas com maior nível de escolaridade apresentaram maior adesão vacinal 15 . Em Israel, a equipe de saúde influenciou no aumento das taxas de vacinação por fornecer informações seguras 16 .…”
Section: Introductionunclassified